Normative Evolution of Child Rights in Nigeria - Emelonye, Uchenna (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
The normative bedrock and corner-stone of modern human rights is the ‘International Bill of Rights’ (IBR) suspended by three-prong legs, one of which is the Universal Declaration of Human Rights (UDHR).[1] While the UDHR did not articulate any child-specific human rights provision, a deductive reading of the broad spectrum of rights guaranteed in the Declaration disposes it as one of the strongest normative frameworks for the protection of child rights. As ‘a first step in a great revolutionary process’, the UDHR was intended not to be a binding legal instrument but instead a declaration of basic principles of human rights and freedoms.[2] In a bid to overcome the weaknesses of the UDHR and create a binding legal instrument, the United Nations Commission on Human Rights drafted a pair of binding covenants to complement the UDHR and constitute two of the three-prong stand of the IBR. They are the International Covenant on Civil and Political Rights (ICCPR)[3] and the International Covenant on Economic Social and Cultural Rights (ICESCR).[4] The ICCPR and ICESCR together with the UDHR form the IBR and jointly precipitated the expansion of international human rights standards in the form of treaties, declarations and conventions.